2016
DOI: 10.1088/1748-605x/12/1/015002
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm prevention of gram-negative bacterial pathogens involved in periprosthetic infection by antibiotic-loaded calcium sulfate beads in vitro

Abstract: Biofilm formation represents a key stage in the pathogenesis of prosthetic infections (PIs). More tolerant to antibiotics than their planktonic counterparts, biofilm bacteria are difficult to eradicate using conventional therapeutic regimes. A common approach in PI management is the adjunctive use of localised antibiotics in addition to systemic administration in an attempt to protect the implant from colonisation by infiltrating bacteria. This study evaluates the antibacterial and antibiofilm efficacy of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 49 publications
4
21
0
Order By: Relevance
“…In this work, compared with the PMMA‐v, the dual carrier‐v can optimize the vancomycin release, especially in the early stages of drug release experiments. Calcium sulfate‐based antibiotic carriers have presented its antibiofilm formation because of its long‐lasting antibacterial capacity [31]. More importantly, the dual carrier‐v can yield synergistic roles.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, compared with the PMMA‐v, the dual carrier‐v can optimize the vancomycin release, especially in the early stages of drug release experiments. Calcium sulfate‐based antibiotic carriers have presented its antibiofilm formation because of its long‐lasting antibacterial capacity [31]. More importantly, the dual carrier‐v can yield synergistic roles.…”
Section: Discussionmentioning
confidence: 99%
“…Another concern associated with localized antibiotic therapy is that of the development of antibiotic resistance if the infecting bacteria are exposed to sub‐MIC concentrations for prolonged periods. In vitro data shows that when bacteria are in biofilms often, depending upon the strain, much higher concentrations of antibiotics are required to achieve clinically relevant reductions than can be achieved systemically, thus localized delivery via impregnated bone cements is a mechanism commonly used by surgeons to increase the antibiotic concentration at the site of infection. A concern with any diffusion based release in which the reservoir is not replenished is that the concentration will inevitably fall below the MIC as a function of time and distance from the reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…Mineral beads such as CS‐B do not play a structural role but have the advantage that they completely dissolve when implanted in soft tissues releasing all antibiotic and thus also negate need for subsequent removal and their small size can be conducive to obtaining high packing density in terms of dead space management in the vicinity of the prosthesis . Previously we have assessed CS‐B loaded with vancomycin hydrochloride (VAN) and tobramycin sulfate (TOB) to prevent or kill biofilms from various Gram positive and negative biofilm forming PJI pathogens using a polystyrene culture dish as a substrate . Here we extend our study to biofilms grown on 316L stainless steel (SS) as a representative orthopaedic metal and compare the efficacy of eradicating P. aeruginosa and S. aureus biofilms using PL alone, CS‐B loaded with VAN and TOB alone and the two treatments (PL and CS‐B) in combination.…”
mentioning
confidence: 99%
“…A biodegradable alternative to PMMA is calcium sulfate, which has long been reported as an effective means of delivering antibiotic 8 - 10 . Its biodegradable nature eliminates the need for subsequent surgical removal, and recent studies have indicated it may be effective tool in preventing the formation of bacterial biofilms 11 , 12 . Calcium sulfate also has the advantage of providing an effective osteoconductive scaffold 13 , supporting new bone growth when implanted in a bone void 14 .…”
Section: Introductionmentioning
confidence: 99%